American black bear (Ursus americanus) as a potential host for Campylobacter jejuni - Craig T. Parker; Sophia Kathariou; William G. Miller; Steven Huynh; Ben Pascoe; Kerry K. Cooper (PLoS ONE, 2025)
The Gram-negative bacterium Campylobacter jejuni is part of the commensal gut microbiota of numerous animal species and a leading cause of bacterial foodborne illness in humans. Most complete genomes of C. jejuni are from strains isolated from human clinical, poultry, and ruminant samples. Here, we characterized and compared the genomes of C. jejuni that were isolated from American black bears in three states in the southeastern United States from 2014 to 2016. Despite the limited sample size (n = 9), the isolates displayed substantial genotypic variability, including eight distinct sequence types (STs) and variable gene content encoding surface glycan structures such as capsular polysaccharides (CPS) and lipooligosaccharides (LOS). Phylogenetic analysis identified several C. jejuni host generalist strains among the isolates from bears that clustered with isolates from domestic poultry, cattle, and environmental sources. Three isolates (SKBC94, SKBC3, SKBC5) clustered with wildlife-associated strains, exhibiting mutations or deletions in loci associated with cytolethal distending toxin production and oxidative stress resistance, potentially influencing host-specific colonization. Additionally, strains SKBC3 and SKBC5 harbored distinct Entner-Doudoroff (E-D) loci, suggesting a potential evolutionary fitness advantage. This study provides the first evidence of C. jejuni colonization in American black bears, highlighting their potential role as reservoirs for diverse C. jejuni lineages from both anthropogenic and environmental sources. Further research is needed to determine the prevalence and host specificity of C. jejuni strains in black bears and their potential implications for public and wildlife health.